Preparation method of heat-resistant flame-retardant foaming hot melt adhesive

By using epoxy resin modified PA6, toughener and synergistic flame retardant in the foamed hot melt adhesive, the problem of degradation of performance of foamed hot melt adhesive in the prior art at high temperature is solved, and the heat resistance and flame retardancy of the material are significantly improved, while ensuring environmental protection and cost-effectiveness.

CN119529757AActive Publication Date: 2025-02-28GUANGZHOU POSEIDON MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411788141.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-28
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The existing foamed hot melt adhesives show decreasing adhesion, deformation and even melting in high temperature environments, and traditional modification methods are difficult to improve heat resistance and flame retardant performance at the same time, and there are problems such as increasing costs, increasing processing difficulty and unfriendly environment.

Method used

Epoxy resin modified PA6 is used as the matrix resin, combined with toughening agents MAH-g-PP and POE, and a mixture of melamine phosphate, modified expanded graphite and red phosphorus is used as flame retardant, and melt kneading, granulation and foaming are carried out through optimized formulation and preparation process to form a heat-resistant flame retardant foam hot melt adhesive.

Benefits of technology

It significantly improves the heat resistance and flame retardancy of the material, maintains stable bonding performance at high temperatures, and reduces production costs, improves the market competitiveness of the product, and meets environmental protection requirements.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of adhesives, and particularly relates to a preparation method of a heat-resistant flame-retardant foaming hot melt adhesive. The hot melt adhesive comprises the following raw materials in parts by mass: 40-50 parts of epoxy resin modified PA6, 5-10 parts of a flexibilizer, 10-15 parts of a flame retardant, 2-4 parts of a nucleating agent, 3-5 parts of a foaming agent, 1-2 parts of a coupling agent, 0.5-1 part of an antioxidant and 0.5-1 part of a lubricant. The preparation method comprises the steps of mixing, melting and mixing, granulating, foaming and the like. By optimizing the formula and the preparation process, the heat resistance and flame retardance of the foaming hot melt adhesive are remarkably improved, good bonding strength is kept, and meanwhile the used raw materials are environmentally friendly and free of pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and in particular relates to a method for preparing a heat-resistant and flame-retardant foaming hot-melt adhesive. Background Art

[0002] Foaming hot melt adhesive is a thermoplastic resin that is melted by heating and then coated or injected, and solidified after cooling to form a foam structure. This structure not only reduces the weight of the material, but also improves the thermal insulation and sound insulation effect of the material. The common foaming hot melt adhesives on the market are mainly made of thermoplastic polymers such as polyethylene (PE), polypropylene (PP), and ethylene-vinyl acetate copolymer (EVA). Although these materials exhibit good physical and mechanical properties and bonding properties at room temperature, when used in high temperature environments, due to the heat resistance temperature limit of the material itself, the bonding force often decreases, deforms, or even melts, which seriously affects the performance of the product.

[0003] In certain specific application scenarios, such as the bonding of automotive interior parts, the fixing of internal components of electronic products, the installation of building exterior wall insulation materials, etc., the foamed hot melt adhesive is required to maintain stable performance at higher temperatures and have a certain flame retardant ability to prevent the occurrence of fire accidents. Traditional modification methods mainly include adding inorganic fillers, organic flame retardants, etc. However, although the heat resistance temperature of most improved foamed hot melt adhesives has been improved, it still cannot meet the application in certain higher temperature environments. In addition, although the addition of some flame retardants can improve the flame retardant level of the material, due to poor compatibility and other reasons, it often leads to a decrease in the mechanical properties of the material. In addition, the improvement methods of the prior art are often accompanied by problems such as increased costs, increased processing difficulties, and environmental unfriendliness.

[0004] In summary, developing a foaming hot melt adhesive that can significantly improve the heat resistance temperature and effectively enhance the flame retardant properties, while ensuring that the comprehensive performance of the material is not affected and meets environmental protection requirements is a technical problem that needs to be solved urgently. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a heat-resistant and flame-retardant foaming hot-melt adhesive to meet the growing market demand for high-performance adhesives.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing a heat-resistant flame-retardant foaming hot melt adhesive, wherein the raw materials include the following components by weight: 40-50 parts of epoxy resin modified PA6, 5-10 parts of toughening agent, 10-15 parts of flame retardant, 2-4 parts of nucleating agent, 3-5 parts of foaming agent, 1-2 parts of coupling agent, 0.5-1 parts of antioxidant, and 0.5-1 parts of lubricant;

[0008] The preparation method comprises the following steps:

[0009] (1) putting all raw materials into a mixer for mixing at a mixer speed of 1000-5000 rpm for 10-20 minutes;

[0010] (2) adding the mixed raw materials into a twin-screw extruder for melt mixing and granulation;

[0011] (3) adding the particles obtained in step (2) into a single screw extruder for foaming, cooling and shaping the foamed material to obtain the heat-resistant and flame-retardant foaming hot melt adhesive.

[0012] Furthermore, the parameters of the twin-screw extruder are set as follows: screw speed: 200-300rpm; feed section temperature: 175-185°C, compression section temperature: 195-205°C, metering section temperature: 210-225°C, die head temperature: 225-230°C; vacuum degree: -0.05--0.1MPa.

[0013] Furthermore, the parameters of the single-screw extruder are set as follows: screw speed: 50-70rpm; feed section temperature: 175-185°C, compression section temperature: 195-205°C, metering section temperature: 210-225°C, die head temperature: 225-230°C; foaming pressure: 8-12MPa.

[0014] Furthermore, the preparation method of the epoxy resin modified PA6 comprises the following steps:

[0015] (i) mixing 40-50 parts of PA6, 2-5 parts of epoxy resin, 0.1-0.3 parts of triphenylphosphine and 0.1-0.2 parts of antioxidant, and then putting the mixture into a twin-screw extruder for melt grafting reaction to obtain a graft copolymer;

[0016] (ii) cooling and granulating the graft copolymer obtained in step (i) to obtain epoxy resin modified PA6.

[0017] Furthermore, the epoxy resin is selected from one or more of bisphenol A epoxy resin, aliphatic epoxy resin, and amino acid epoxy resin.

[0018] Furthermore, the antioxidant is selected from one or more of antioxidant 1010, antioxidant 168, dilauryl thiodipropionate, diphenylamine, and antioxidant 1076.

[0019] Furthermore, the toughening agent is maleic anhydride grafted polypropylene (MAH-g-PP) and ethylene-octene copolymer (POE), and the mass ratio of the two is 1: (0.8-1.2).

[0020] MAH-g-PP can form chemical bonds with the matrix resin through maleic anhydride groups, enhance interfacial bonding, improve compatibility with epoxy resin modified PA6, form a continuous phase interface, and thus improve the overall performance of the material. POE is an elastomer with excellent flexibility and tear resistance. It can effectively disperse stress and prevent crack expansion, thereby improving the toughness of the material. The combination of MAH-g-PP and POE can produce a synergistic toughening effect. MAH-g-PP enhances interfacial bonding through chemical bonding, while POE improves flexibility through physical dispersion. This synergistic effect enables the material to better disperse stress and prevent crack generation and expansion when subjected to external forces. By adjusting the mass ratio of MAH-g-PP and POE, the toughness can be improved while keeping other properties of the material (such as heat resistance and flame retardancy) unaffected. The combination of MAH-g-PP and POE can also improve the heat resistance of the material. MAH-g-PP enhances interfacial bonding through chemical bonding and improves the heat stability of the material. The elasticity of POE can prevent brittle cracking at high temperatures, thereby improving the overall heat resistance.

[0021] Furthermore, the flame retardant is a mixture of melamine phosphate, modified expanded graphite and red phosphorus, with a mass ratio of (4-6): (3-4): (1-2).

[0022] Furthermore, the preparation method of the modified expanded graphite comprises the following steps:

[0023] (a) mixing expanded graphite with sulfuric acid having a mass concentration of 98%, so that the expanded graphite is completely immersed in the sulfuric acid, and placing the mixture in an ice water bath;

[0024] (b) adding nitric acid having a mass concentration of 65% dropwise to the mixture, stirring the mixture in an ice-water bath for 20-40 minutes after the addition is complete, then transferring the mixture to room temperature and stirring the mixture for 50-70 minutes;

[0025] (c) After the reaction in step (b) is completed, the solid product is separated by centrifugation, and the solid product is washed with deionized water until the filtrate is neutral;

[0026] (d) re-dispersing the washed solid product in deionized water, ultrasonically treating it to ensure uniform dispersion, adding silane coupling agent KH550, continuing ultrasonic treatment, transferring the ultrasonically treated mixture to a water bath, heating it to 50-70° C., stirring and reacting, and obtaining a modified expanded graphite suspension;

[0027] (e) drying the modified expanded graphite suspension, grinding it, and passing it through a 100-mesh sieve to obtain the modified expanded graphite.

[0028] Furthermore, the mass volume ratio of the expanded graphite to 98% sulfuric acid is 1 g: (4-6) mL, and the mass volume ratio of the expanded graphite to 65% nitric acid is 1 g: (1-2) mL.

[0029] Furthermore, the mass of the silane coupling agent KH550 in step (d) is 15-25% of the expanded graphite; the ultrasonic treatment is continued for 20-40 minutes after the addition of the silane coupling agent KH550; and the stirring reaction time in step (d) is 1.5-2.5 hours.

[0030] Furthermore, in step (e), the drying temperature is 60-70° C., and the drying time is 20-30 hours.

[0031] The modified expanded graphite of the present invention can expand rapidly at high temperature to form a porous carbon layer, which can effectively isolate oxygen and heat, prevent the spread of flames, and improve the flame retardancy of the material; the formed carbon layer has good thermal insulation performance, can significantly reduce the temperature inside the material, and prevent the internal material from being pyrolyzed and burned; the formed carbon layer can also physically shield the flame to prevent the flame from directly contacting the substrate, thereby improving the fire resistance of the material. Through the modification of silane coupling agent, the compatibility of the modified expanded graphite with the matrix resin is greatly improved, the interface bonding force is enhanced, and the flame retardant effect is improved. The combination of melamine phosphate, modified expanded graphite and red phosphorus can produce a synergistic effect and jointly improve the flame retardancy of the material. Melamine phosphate and red phosphorus form a carbonized layer through chemical action, and the modified expanded graphite forms a heat insulation layer through physical expansion. The three complement each other to form a multiple flame retardant mechanism. Reasonable design of the three ratios can simultaneously improve the heat resistance, flame retardancy and mechanical properties of the material. In addition, red phosphorus, melamine phosphate and modified expanded graphite are more environmentally friendly than halogen flame retardants, do not produce toxic gases when burned, and meet environmental protection requirements.

[0032] Furthermore, the nucleating agent is selected from one or more of nano silicon dioxide, talc, calcium carbonate, sodium diphenyl acetate, and mica powder.

[0033] Furthermore, the foaming agent is selected from one or more of ammonium azodicarboxylate, sodium bicarbonate, citric acid, and sodium nitrite.

[0034] Furthermore, the coupling agent is selected from one or more of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent.

[0035] Furthermore, the antioxidant is selected from one or more of antioxidant 1010, antioxidant 168, dilauryl thiodipropionate, diphenylamine, and antioxidant 1076.

[0036] Furthermore, the lubricant is selected from one or more of zinc stearate, calcium stearate, polyethylene wax, and polypropylene wax.

[0037] The heat-resistant flame-retardant foaming hot-melt adhesive of the present invention uses epoxy resin modified PA6 as a matrix resin, and the introduction of epoxy groups can further improve the chemical bonding and physical adsorption between the hot-melt adhesive and the substrate surface, thereby improving the bonding performance of the hot-melt adhesive. In addition, epoxy resin can improve the toughness of PA6, making it difficult to break when impacted or stretched. When epoxy resin modified PA6 is used as a matrix resin, it can be coordinated with the flame retardant of the present invention (a mixture of melamine phosphate, modified expanded graphite and red phosphorus) to further improve the flame retardant effect. The modified expanded graphite is treated with a silane coupling agent to form a chemical bond with the epoxy group in the epoxy resin, further enhance the interfacial bonding force, and improve the compatibility. The active groups in melamine phosphate and red phosphorus can react chemically with the epoxy group in the epoxy resin to form a stable network structure and improve the overall performance of the material. The addition of MAH-g-PP and POE can further improve the cohesion and toughness of the material. The components in the formula of the present invention have synergistic effects through chemical bonding, physical dispersion, multiple flame retardant mechanisms, etc., which significantly improves the heat resistance, flame retardancy, mechanical properties and processing properties of the material.

[0038] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0039] The present invention provides a method for preparing a heat-resistant and flame-retardant foaming hot melt adhesive, which significantly improves the heat resistance and flame retardancy of the material by optimizing the formula and preparation process. Compared with the traditional foaming hot melt adhesive, the product of the present invention has a higher softening point at high temperature and stronger flame retardancy, while maintaining good bonding performance and having environmental protection characteristics. In addition, through reasonable formula design and preparation process, the present invention reduces production costs and improves the market competitiveness of the product. DETAILED DESCRIPTION

[0040] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Unless otherwise specified, the raw materials used in the examples are all common commercially available products. The following is an exemplary description:

[0042] Polyamide 6 (PA6) was purchased from Zhejiang Xinhecheng Co., Ltd., PA6-1013;

[0043] Epoxy resin was purchased from Baling Petrochemical, E-51;

[0044] Maleic anhydride grafted polypropylene (MAH-g-PP) was purchased from the New Materials Research Institute of Beijing University of Chemical Technology, MAH-g-PP-100;

[0045] Ethylene-octene copolymer (POE) was purchased from Shanghai Petrochemical Co., Ltd., POE-8150;

[0046] Ethylene-vinyl acetate copolymer (EVA) was purchased from Jiangsu Sailbon Petrochemical Co., Ltd., EVA-1102;

[0047] Talc powder was purchased from Liaoning Haicheng Talc Group Co., Ltd., HT-100, with a particle size of about 1 μm;

[0048] Melamine phosphate was purchased from Zhejiang Longsheng Group Co., Ltd., MPP-100, with a particle size of about 5 μm;

[0049] Red phosphorus was purchased from Shandong Ruifeng Polymer Materials Co., Ltd., RF-RP-100;

[0050] Expanded graphite was purchased from Qingdao Huagao Graphene Technology Co., Ltd., HG-EG-100, with a particle size of about 10 μm and an expansion multiple of ≥200 times.

[0051] Example 1

[0052] The present embodiment provides a method for preparing a heat-resistant and flame-retardant foaming hot-melt adhesive, wherein the raw materials include the following components in parts by mass: 45 parts of epoxy resin modified PA6, 8 parts of a toughening agent (MAH-g-PP and POE in a mass ratio of 1:1), 13 parts of a flame retardant, 3 parts of a nucleating agent (talc), 4 parts of a foaming agent (ammonium azodicarboxylate), 1.5 parts of a coupling agent (KH550), 0.8 parts of an antioxidant (antioxidant 1010), and 0.8 parts of a lubricant (zinc stearate).

[0053] The preparation method of the epoxy resin modified PA6 comprises the following steps:

[0054] (i) 45 parts of PA6, 4 parts of epoxy resin (Epoxy Resin E-51), 0.2 parts of triphenylphosphine and 0.1 parts of antioxidant 1010 were mixed and put into a twin-screw extruder for melt grafting reaction. The screw speed was 200 rpm, and the temperatures of each zone were: 180° C. in the feeding section, 200° C. in the compression section, 220° C. in the metering section, and 230° C. in the die head, to obtain a graft copolymer;

[0055] (ii) cooling and granulating the graft copolymer obtained in step (i) through a water-cooled pelletizer to obtain epoxy resin-modified PA6.

[0056] The flame retardant is a mixture of melamine phosphate, modified expanded graphite and red phosphorus, with a mass ratio of 5:3.5:1.5.

[0057] The preparation method of the modified expanded graphite comprises the following steps:

[0058] (a) Add 10 g of expanded graphite to a clean beaker, then add 50 mL of 98% sulfuric acid to the beaker so that the expanded graphite is completely immersed in the sulfuric acid, and place the beaker in an ice water bath;

[0059] (b) 15 mL of 65% nitric acid was added dropwise to the beaker over a period of about 5 minutes. After the addition was complete, the mixture was stirred in an ice-water bath for 30 minutes. The beaker was then transferred to room temperature and stirred for 60 minutes.

[0060] (c) After the reaction in step (b) is completed, the solid product is separated by centrifugation, and the solid product is repeatedly washed with deionized water until the filtrate is neutral;

[0061] (d) the washed solid product was redispersed in 100 mL of deionized water, and ultrasonically treated for 10 minutes to uniformly disperse the solid product in the deionized water, 2 g of silane coupling agent KH550 was added, and ultrasonic treatment was continued for 30 minutes, and the ultrasonically treated mixture was transferred to a water bath, heated to 60° C., and stirred for reaction for 2 hours to obtain a modified expanded graphite suspension;

[0062] (e) drying the modified expanded graphite suspension at 60° C. for 24 hours, grinding it with a grinder, and passing it through a 100-mesh sieve to obtain the modified expanded graphite.

[0063] The preparation method of the heat-resistant flame-retardant foaming hot-melt adhesive comprises the following steps:

[0064] (1) Weigh the raw materials according to the ratio, put all the raw materials into the mixer for mixing, set the mixer speed to 2000 rpm, and the mixing time to 15 minutes to ensure that all components are fully dispersed;

[0065] (2) adding the mixed raw materials into a twin-screw extruder for melt mixing, and setting the following parameters for the twin-screw extruder: screw speed: 240 rpm; feeding section temperature: 180° C., compression section temperature: 200° C., metering section temperature: 220° C., die head temperature: 230° C.; vacuum degree: -0.08 MPa. The materials mixed in the twin-screw extruder are pelletized by a water-cooled pelletizer to obtain pellets with uniform particle size;

[0066] (3) Add the particles obtained in step (2) into a single-screw extruder for foaming. The single-screw extruder is set with the following parameters: screw speed: 60 rpm; feed section temperature: 180°C, compression section temperature: 200°C, metering section temperature: 220°C, die head temperature: 230°C, foaming pressure: 10 MPa. The foamed material is cooled and shaped in a cold water tank. The water temperature is controlled at 20°C and the cooling time is 1 minute to ensure that the material is completely solidified. The cooled material is cut into the required size and shape to obtain a heat-resistant and flame-retardant foaming hot melt adhesive.

[0067] Example 2

[0068] This embodiment provides a method for preparing a heat-resistant flame-retardant foaming hot melt adhesive, which is different from Example 1 in that the raw materials include the following components by mass: 50 parts of epoxy resin modified PA6, 5 parts of toughening agent (MAH-g-PP and POE in a mass ratio of 1:1), 13 parts of flame retardant, 3 parts of nucleating agent (nanosilica), 4 parts of foaming agent (sodium bicarbonate), 1.5 parts of coupling agent (KH550), 0.8 parts of antioxidant (antioxidant 1010), and 0.8 parts of lubricant (polyethylene wax). The flame retardant is a mixture of melamine phosphate, modified expanded graphite and red phosphorus, with a mass ratio of 5:4:1. The rest is the same as Example 1.

[0069] Comparative Example 1

[0070] This comparative example provides a method for preparing a heat-resistant and flame-retardant foamed hot-melt adhesive, which differs from Example 1 in that epoxy resin-modified PA6 is replaced by EVA (ethylene-vinyl acetate copolymer), and the rest is the same as Example 1.

[0071] Comparative Example 2

[0072] This comparative example provides a method for preparing a heat-resistant and flame-retardant foaming hot-melt adhesive, which is different from Example 1 in that the toughening agent is 8 parts of POE, and the rest is the same as Example 1.

[0073] Comparative Example 3

[0074] This comparative example provides a method for preparing a heat-resistant and flame-retardant foamed hot-melt adhesive, which is different from Example 1 in that the flame retardant is a mixture of melamine phosphate, modified expanded graphite and red phosphorus in a mass ratio of 5:1:1, and the rest is the same as Example 1.

[0075] Comparative Example 4

[0076] This comparative example provides a method for preparing a heat-resistant and flame-retardant foamed hot-melt adhesive, which is different from Example 1 in that the flame retardant is a mixture of decabromodiphenyl ether, aluminum hydroxide, and zinc borate in a mass ratio of 5:3.5:1.5, and the rest is the same as Example 1.

[0077] Comparative Example 5

[0078] This comparative example provides a method for preparing a heat-resistant and flame-retardant foamed hot-melt adhesive, which is different from Example 1 in that the expanded graphite in the flame retardant is not modified, and the rest is the same as Example 1.

[0079] Comparative Example 6

[0080] This comparative example provides a method for preparing a heat-resistant and flame-retardant foamed hot-melt adhesive, which differs from Example 1 in that the epoxy resin-modified PA6 is replaced with unmodified PA6, and the rest is the same as Example 1.

[0081] Performance Testing

[0082] The peel strength, softening point and oxygen index of the hot melt adhesives prepared in Examples 1-2 and Comparative Examples 1-6 were tested.

[0083] Test method for peel strength: Apply the hot melt adhesive to be tested between two 25mm×200mm standard stainless steel plates with a thickness of about 1mm, press them together and cure them at room temperature (25℃) for 24 hours. Fix the sample on an electronic universal testing machine, set the peel speed to 100mm / min, record the peel force, and calculate the peel strength.

[0084] Testing method for softening point: Heat the hot melt adhesive to be tested to a flowing state, pour it into a standard ring mold, cool it to room temperature and demold it to obtain a sample, place the prepared sample on the bracket of the softening point tester, ensure that the bottom of the sample is in good contact with the bracket, set the water bath temperature of the tester to the initial temperature of 5°C, place the steel ball in the ball holder above the sample, turn on the tester, heat the water bath evenly at a speed of 5°C / min, observe and record the temperature when the steel ball passes through the sample and touches the bottom steel plate, which is the softening point of the hot melt adhesive.

[0085] Oxygen index testing method: Make the hot melt adhesive to be tested into a standard sample with a size of 150mm×10mm×3mm, fix the sample in the fixture of the oxygen index tester, ensure that the sample is suspended vertically, set the oxygen concentration of the tester to the initial value of 21%, use an igniter to ignite the upper end of the sample, observe and record the burning conditions of the sample, if the sample continues to burn for more than 3 seconds after the igniter is removed, increase the oxygen concentration, if the sample goes out immediately after the igniter is removed, reduce the oxygen concentration, and gradually adjust the oxygen concentration until a critical value is found so that the sample can just continue to burn for 3 seconds after the igniter is removed, record the critical oxygen concentration, which is the oxygen index of the hot melt adhesive.

[0086] The test results are shown in Table 1.

[0087] Table 1 Performance test results

[0088] sample Peel strength (N / mm) Softening point(℃) Oxygen index (%) Example 1 4.5 120 32.6 Example 2 4.3 118 31.9 Comparative Example 1 3.3 105 31.4 Comparative Example 2 3.7 112 31.6 Comparative Example 3 4.5 110 29.3 Comparative Example 4 4.6 92 24.0 Comparative Example 5 4.2 102 27.1 Comparative Example 6 3.9 109 28.2

[0089] It can be seen from the above test results that the hot melt adhesive prepared by the present invention has excellent bonding strength, heat resistance and flame retardancy. In Comparative Example 1, epoxy resin modified PA6 is replaced by EVA. EVA has poor compatibility with other components, and the interface bonding formed is weak, resulting in decreased peel strength and flame retardancy; EVA has a lower melting point than PA6, resulting in a decrease in softening point. In Comparative Example 2, the toughening agent is changed from a mixture of MAH-g-PP and POE to a single POE. MAH-g-PP enhances the interface bonding through chemical bonding, while POE mainly provides flexibility and lacks chemical bonding. The mixture of MAH-g-PP and POE can improve the cohesion of the material, while a single POE cannot provide the same effect, resulting in a decrease in peel strength; MAH-g-PP can promote the crystallization of epoxy resin modified PA6 and improve heat resistance. MAH-g-PP can also promote the dispersion of flame retardants and improve the flame retardant effect, while POE has little effect on crystallinity and the dispersion of flame retardants. Comparative Example 3 changes the mass ratio of each component of the flame retardant, especially reduces the amount of modified expanded graphite, which expands at high temperatures to form a protective layer, improves heat resistance and flame retardancy, and reducing its amount will significantly affect heat resistance and flame retardancy. Comparative Example 4 replaces the type of flame retardant, and heat resistance and flame retardancy are significantly reduced, indicating that the effects of decabromodiphenyl ether, aluminum hydroxide, and zinc borate as flame retardants are obviously not as good as the flame retardant of the present invention. Comparative Example 5 uses unmodified expanded graphite, and the compatibility and interface bonding of unmodified expanded graphite with epoxy resin modified PA6 are poor, and the expansion effect is poor at high temperatures, and an effective protective layer cannot be formed. Therefore, the bonding performance, heat resistance and flame retardancy are all poor. Comparative Example 6 uses unmodified PA6, and its flame retardancy is significantly reduced. The reason is that the interface bonding force between the unmodified PA6 and the flame retardant is weak, and the interface separation is easy to occur at high temperature, causing the flame retardant to fall off or fail, thereby reducing the flame retardant performance. This further proves that the flame retardant and the base resin of the present invention need to be used at the same time to produce a better effect.

[0090] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a heat-resistant flame-retardant foaming hot melt adhesive, wherein the raw materials include the following components by mass: 40-50 parts of epoxy resin modified PA6, 5-10 parts of toughening agent, 10-15 parts of flame retardant, 2-4 parts of nucleating agent, 3-5 parts of foaming agent, 1-2 parts of coupling agent, 0.5-1 parts of antioxidant, and 0.5-1 parts of lubricant; The preparation method comprises the following steps: (1) putting all raw materials into a mixer for mixing at a mixer speed of 1000-5000 rpm for 10-20 minutes; (2) adding the mixed raw materials into a twin-screw extruder for melt mixing and granulation; (3) adding the particles obtained in step (2) into a single screw extruder for foaming, cooling and shaping the foamed material to obtain the heat-resistant and flame-retardant foaming hot melt adhesive.

2. The preparation method according to claim 1, characterized in that: The preparation method of the epoxy resin modified PA6 comprises the following steps: (i) mixing 40-50 parts of PA6, 2-5 parts of epoxy resin, 0.1-0.3 parts of triphenylphosphine and 0.1-0.2 parts of antioxidant, and then putting the mixture into a twin-screw extruder for melt grafting reaction to obtain a graft copolymer; (ii) cooling and granulating the graft copolymer obtained in step (i) to obtain epoxy resin modified PA6.

3. The preparation method according to claim 2, characterized in that: The epoxy resin is selected from one or more of bisphenol A epoxy resin, aliphatic epoxy resin and amino acid epoxy resin.

4. The preparation method according to claim 1, characterized in that: The toughening agent is maleic anhydride grafted polypropylene and ethylene-octene copolymer, and the mass ratio of the two is 1: (0.8-1.2).

5. The preparation method according to claim 1, characterized in that: The flame retardant is a mixture of melamine phosphate, modified expanded graphite and red phosphorus, with a mass ratio of (4-6): (3-4): (1-2).

6. The preparation method according to claim 5, characterized in that: The preparation method of the modified expanded graphite comprises the following steps: (a) mixing expanded graphite with sulfuric acid having a mass concentration of 98%, so that the expanded graphite is completely immersed in the sulfuric acid, and placing the mixture in an ice water bath; (b) adding nitric acid having a mass concentration of 65% dropwise to the mixture, stirring the mixture in an ice-water bath for 20-40 minutes after the addition is complete, then transferring the mixture to room temperature and stirring the mixture for 50-70 minutes; (c) After the reaction in step (b) is completed, the solid product is separated by centrifugation, and the solid product is washed with deionized water until the filtrate is neutral; (d) re-dispersing the washed solid product in deionized water, ultrasonically treating it to ensure uniform dispersion, adding silane coupling agent KH550, continuing ultrasonic treatment, transferring the ultrasonically treated mixture to a water bath, heating it to 50-70° C., stirring and reacting, and obtaining a modified expanded graphite suspension; (e) drying the modified expanded graphite suspension, grinding it, and passing it through a 100-mesh sieve to obtain the modified expanded graphite.

7. The preparation method according to claim 6, characterized in that: The mass volume ratio of the expanded graphite to 98% sulfuric acid is 1 g: (4-6) mL, and the mass volume ratio of the expanded graphite to 65% nitric acid is 1 g: (1-2) mL.

8. The preparation method according to claim 6, characterized in that: The mass of the silane coupling agent KH550 in step (d) is 15-25% of the expanded graphite; after adding the silane coupling agent KH550, the ultrasonic treatment is continued for 20-40 minutes; and the stirring reaction time in step (d) is 1.5-2.5 hours.

9. The preparation method according to claim 5, characterized in that: The drying temperature in step (e) is 60-70° C. and the drying time is 20-30 hours.

10. The preparation method according to claim 1, characterized in that: The nucleating agent is selected from one or more of nano silicon dioxide, talc, calcium carbonate, sodium diphenyl acetate, and mica powder; the foaming agent is selected from one or more of ammonium azodicarboxylate, sodium bicarbonate, citric acid, and sodium nitrite; the coupling agent is selected from one or more of silane coupling agent, titanate coupling agent, and aluminate coupling agent; the antioxidant is selected from one or more of antioxidant 1010, antioxidant 168, dilauryl thiodipropionate, diphenylamine, and antioxidant 1076; the lubricant is selected from one or more of zinc stearate, calcium stearate, polyethylene wax, and polypropylene wax.

Citation Information

Patent Citations

  • High-efficiency flame-retardant PP composition special for LFT-D

    CN107722450A

  • Halogen-free flame-retarding polyamide material and preparation method thereof

    CN109370207A

  • Low-gloss halogen-free flame-retardant alloy material and preparation method thereof

    CN112321942A

  • Dispersant for solid-containing phenolic foams

    CN118725502A

  • Thermal smelting adhesive based on polyamide block graft copolymer

    CN1441023A

Cited By

  • Fire-resistant flame-retardant PP composite material for new energy battery shell and preparation method thereof

    CN121021981A